2020
DOI: 10.3389/fmars.2020.00119
|View full text |Cite
|
Sign up to set email alerts
|

Novel ABCB1 and ABCC Transporters Are Involved in the Detoxification of Benzo(α)pyrene in Thick Shell Mussel, Mytilus coruscus

Abstract: ATP-binding cassette (ABC) transporters play an essential role in xenobiotic resistance through transporting xenobiotics into or out of cells. However, their functional role in mollusk's defense against polycyclic aromatic hydrocarbons (PAHs) remains unclear. In the present study, novel McoABCB1 and McoABCC transporters were identified in the gills of Mytilus coruscus, and their benzo(α)pyrene (Bap) detoxification function was determined by qRT-PCR and efflux assays. McoABCB1 and McoABCC genes were constitutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Especially, micro-RNAs(miRNAs) extensively affect their protein level through interaction with target mRNA [ 38 ]. Previous research reported B[a]P induces the mRNA expression of ABCCs, while inhibiting the protein level and function of ABCC transporters [ 39 , 40 ]. In our results, quercetin or isorhamnetin in combination with B[a]P increased both mRNA and protein levels of ABCCs compared to only the B[a]P treated group ( Figure 4 and Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Especially, micro-RNAs(miRNAs) extensively affect their protein level through interaction with target mRNA [ 38 ]. Previous research reported B[a]P induces the mRNA expression of ABCCs, while inhibiting the protein level and function of ABCC transporters [ 39 , 40 ]. In our results, quercetin or isorhamnetin in combination with B[a]P increased both mRNA and protein levels of ABCCs compared to only the B[a]P treated group ( Figure 4 and Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Following GSH-conjugation with B[a]P metabolites via phase II detoxifying enzymes, it is excreted by transporter genes, such as ABCC1 and ABCC2 [17]. Previous studies have showed that ABCC transporters are required to detoxify B[a]P [18]. The knockdown of ABCC2 increases the concentration of B[a]P metabolites in a variety of organs [19].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, some studies suggest their involvement in B[a]P excretion. For instance, in various species, ABC transporters have been identified as responsible for eliminating B[a]P metabolites [48,49]. Furthermore, B[a]P has been shown to reduce the expression levels of ABCA12 [50] and decrease the protein expression level of ABCC1 [51], suggesting a potential hindrance in the proper removal of detoxified B[a]P metabolites from cells due to reduced transporter expression.…”
Section: Metabolism and Excretion Of B[a]p And Their Hepatic Conseque...mentioning
confidence: 99%